2012
DOI: 10.1080/17451000.2011.627922
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of metazooplankton in coastal sub-Antarctic waters (Beagle Channel)

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of any instructions, formulae, and drug doses should be independently verified with primary sources. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 37 publications
5
22
1
1
Order By: Relevance
“…Copepods were the dominant metazooplankton group at the study site, as observed in other temperate coastal regions (Hopcroft et al 2001, Aguirre et al 2012). Copepods play a key role in the pelagic carbon flux because of their capability of taking up energy from the microbial food web and transferring it to higher trophic levels (Turner 2004, Viñas et al 2013.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Copepods were the dominant metazooplankton group at the study site, as observed in other temperate coastal regions (Hopcroft et al 2001, Aguirre et al 2012). Copepods play a key role in the pelagic carbon flux because of their capability of taking up energy from the microbial food web and transferring it to higher trophic levels (Turner 2004, Viñas et al 2013.…”
Section: Discussionmentioning
confidence: 64%
“…Los copépodos fueron el grupo de metazooplancton dominante en el sitio estudiado, como se ha observado en otras regiones costeras templadas (Hopcroft et al 2001, Aguirre et al 2012. Los copépodos juegan un papel clave en el flujo de carbono pelágico debido a su capacidad para tomar la energía de la red trófica microbiana y transferirla a los Table 3.…”
Section: Discussionunclassified
“…This bottom-up regulation has been reported frequently in populations of appendicularians (BÅMSTEDT et al, 2005). AGUIRRE et al (2012) observed that the highest densities of F. borealis in the Beagle Channel during spring coincided with the maximum values of surface chlorophyll-a. In the present study, the highest densities of F. borealis were registered in spring and summer while the maximum values of chlorophyll-a occurred in late winter.…”
Section: Discussionmentioning
confidence: 89%
“…During the seasonal cycle at a Buenos Aires coastal station (38º28´S, 57º41´W), its highest densities occurred during the autumn-winter period, coinciding with the lowest temperatures (CAPITANIO et al, 2008). Also, in the subAntarctic region, AGUIRRE et al (2012), who studied the seasonal variation in the composition and abundance of metazooplankton in different bays of the Beagle Channel, reported that this species is widely distributed in these coastal zones. F. borealis was an important component of zooplankton in spring (November), coinciding with maximum values of chlorophyll-a.…”
Section: Introductionmentioning
confidence: 99%
“…The Beagle Channel is located at the southern tip of South America and is a sub-Antarctic coastal marine-estuarine environment (Isla et al 1999;Aguirre et al 2012). The environmental conditions are markedly seasonal: sea surface temperature in the lower intertidal zone ranges from 5.2°C in August to 9.5°C in January (Laboratorio Biología de Crustáceos, CADIC, unpublished data).…”
Section: Study Areamentioning
confidence: 99%